2018
DOI: 10.1093/nar/gky288
|View full text |Cite
|
Sign up to set email alerts
|

Emerin modulates spatial organization of chromosome territories in cells on softer matrices

Abstract: Cells perceive and relay external mechanical forces into the nucleus through the nuclear envelope. Here we examined the effect of lowering substrate stiffness as a paradigm to address the impact of altered mechanical forces on nuclear structure-function relationships. RNA sequencing of cells on softer matrices revealed significant transcriptional imbalances, predominantly in chromatin associated processes and transcriptional deregulation of human Chromosome 1. Furthermore, 3-Dimensional fluorescence in situ hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 149 publications
0
20
0
Order By: Relevance
“…Depletion of nuclear structural proteins, such as lamin A/C, may explain two major hallmarks of cancer: aberrations in nuclear morphology and aneuploidy . It also affects another hallmark of cancer cells, which is chromosome aberrations . Mutations or loss of nuclear structural proteins and other cellular factors also affect the positioning of diverse human genes, the regulation of cell process, chromatin loop domains, and chromosome dynamics, which we discuss here.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Depletion of nuclear structural proteins, such as lamin A/C, may explain two major hallmarks of cancer: aberrations in nuclear morphology and aneuploidy . It also affects another hallmark of cancer cells, which is chromosome aberrations . Mutations or loss of nuclear structural proteins and other cellular factors also affect the positioning of diverse human genes, the regulation of cell process, chromatin loop domains, and chromosome dynamics, which we discuss here.…”
Section: Introductionmentioning
confidence: 96%
“…25,26 It also affects another hallmark of cancer cells, which is chromosome aberrations. [27][28][29] Mutations or loss of nuclear structural proteins and other cellular factors also affect the positioning of diverse human genes, 30 the regulation of cell process, 31,32 chromatin loop domains, 33,34 and chromosome dynamics, 35 which we discuss here.…”
Section: Introductionmentioning
confidence: 99%
“…This was consistent with enrichment in nucleoplasmic lamin levels in cells cultured on softer matrices. Remarkably, lamins were restored to the nuclear envelope in cells transferred from softer to stiffer substrates [145]. Taken together, lamins respond to external mechanical signals in a phosphorylation-dependent mechanism.…”
Section: Lamins In Mechano-signallingmentioning
confidence: 85%
“…Guilluy and colleagues showed that the phosphorylation of Y74 and Y95 of emerin residues by Src mediates the mechanical adaptation of nuclei to mechanical force [71]. Some recent evidence demonstrate that the cells cultured on soft matrices induced emerin phosphorylation and the mislocalization of nuclear envelope proteins in the nucleoplasm [72]. The authors also suggest that emerin is able to reorganize the chromosome territories in cells on softer matrix and they speculate that emerin phosphorylation acts as an upstream regulator of lamin localization resulting in substantial changes of the transcriptional regulation in a substrate stiffness-dependent manner [72].…”
Section: Interaction With the Nuclear Envelope Protein Emerinmentioning
confidence: 99%